28.3k views
5 votes
For the given equation: y = 7 - 2x,

when x = 1, y =

User Gogaz
by
4.7k points

2 Answers

1 vote
Y=5 :)) hope I helped I tried at least
6 votes

Answer:

y = 5

General Formulas and Concepts:

Pre-Alg

  • Order of Operations: BPEMDAS

Explanation:

Step 1: Define

y = 7 - 2x

x = 1

Step 2: Find y

  1. Substitute in x: y = 7 - 2(1)
  2. Multiply: y = 7 - 2
  3. Subtract: y = 5
User CoPLaS
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.